PALÉOENVIRONNEMENTS ET PALÉOCLIMATS DURANT LE PLÉISTOCENE SUPERIEUR ET L’HOLOCENE SUR LA DORSALE OCCIDENTALE DU KIVU EN RÉPUBLIQUE DÉMOCRATIQUE DU CONGO - Chantal, Kabonyi Nzabandora; Emile, Roche; Philippe, Gerrienne (European Scientific Journal, ESJ, 2015)
Palynological studies of sedimentary sequences issued from swamps located in the highlands of the KBNP (Kahuzi-Biega National Park) on the western divide of Kivu in Eastern D.R. Congo, revealed important environmental events that occurred during Upper Quaternary. The Cishaka sequence covers the last 35000 years. In the Upper Pleistocene, during the “Kalambo Interstadial” period (32000- 26000 years BP), a mixed forest spread out under a moderately warm-wet climate. In the course of the “Mount Kenya Hypothermal” regressive phase (25000- 15000 years BP), in the “Last Glacial Maximum” (20000-18000 years BP) takes place an exceptional expansion of open grasslands that evidenced an important drought. After that, the revival of an afro-montane forest growing under cold-wet climatic conditions is recorded, but that one is temporarily interrupted by theYoung Dryas dry pulse. At the Humid Holocene Period (10000-7000 years BP), with the increase of rainfall, the Kivu Lake level is raising when the swamps in the highlands are transformed in lakes. Around 6500 yrs BP, the afro-montane rainforest invaded by afro-subalpine taxa turns into a secondary mixed forest as the result of a climatic deterioration. At 4000 yrs BP, an important spreading of grasslands in the highlands and of savannas in the lowlands testifies that an aridity peak occurs at the time. The changes that occurs from 3000 years BP to 2000 years BP in the afromontane forest suggests a climatic instability that moreover speeds up erosion processes. In the course of the first millennium AD, rainforest grows again; that event being shortly interrupted by a drought around 500 years AD. At the beginning of the second millennium AD, the lower belt of the forest is yet deteriorated by anthropic action while middle and upper belts are stable but marked by a fresh climate resulting of the “Mount Kenya Neoglacial” influence. From 17th – 18th centuries, human impact increases progressively in the highlands.